The Performance of Literate Practices: Rhetoric, Writing, and Stand-up Comedy - J. Michael Rifenburg (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
An analysis of a comedian’s composition of comedy routines leads to valuable implications about the performative aspects of revision.